Endocarditis due to Coccidioides spp: The Seventh Case. (1st July 2015) - Horng, Lily M.; Yaghoubian, Shadi; Ram, Arleen; Johnson, Royce; Castro, Luis; Kuo, Jenny; Deresinski, Stan
Abstract: Coccidioides, a dimorphic fungus endemic within the Americas, primarily causes pulmonary disease but may disseminate. We describe a case of confirmed Coccidioides endocarditis, the seventh reported in literature. Coccidioides endocarditis often requires tissue diagnosis and combined surgical and medical treatment.